1998
DOI: 10.1016/s0006-3495(98)77750-1
|View full text |Cite
|
Sign up to set email alerts
|

Severing of F-Actin by the Amino-Terminal Half of Gelsolin Suggests Internal Cooperativity in Gelsolin

Abstract: Gelsolin is a Ca2+-regulated actin-binding protein that can sever, cap, and nucleate growth from the pointed ends of actin filaments. In this study we have measured the binding of the amino-terminal half of gelsolin, G1-3, to pyrene-labeled F-actin as a function of Ca2+ concentration. The rate of binding is shown to be dependent on micromolar concentrations of Ca2+. Independent experiments demonstrate that conformational changes in G1-3 are induced by micromolar concentrations of Ca2+. Titrations of pyrene-F-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 28 publications
8
43
0
1
Order By: Relevance
“…Both Kid fragments moved smoothly and stably for several micrometers, showing that the second microtubule-binding site does not inhibit the motility of Kid. Some of these movements may be induced by several Kid molecules because it has been reported that the plural gelsolin molecules bound to the same actin filament (29). Therefore, it is unclear from our assay whether Kid is a processive motor or not.…”
Section: Resultsmentioning
confidence: 95%
“…Both Kid fragments moved smoothly and stably for several micrometers, showing that the second microtubule-binding site does not inhibit the motility of Kid. Some of these movements may be induced by several Kid molecules because it has been reported that the plural gelsolin molecules bound to the same actin filament (29). Therefore, it is unclear from our assay whether Kid is a processive motor or not.…”
Section: Resultsmentioning
confidence: 95%
“…A truncated ⑀-amino rhodamine-labeled peptide (1-25 rhod-t␤ 4 peptide) was produced synthetically with a sequence that corresponds to the N-terminal 25 residues of thymosin ␤ 4 , SDKPDMAEIEKFDKSKLKK-TETQEK-rhodamine. Human recombinant gelsolin was truncated to the N-terminal 406 residues (identified here as gelsolin segment 1-3) prior to expression so as to eliminate the dependence of F-actin binding on calcium (27).…”
Section: Methodsmentioning
confidence: 99%
“…A truncated ⑀-amino rhodamine-labeled peptide (1-25 rhod-t␤ 4 peptide) was produced synthetically with a sequence that corresponds to the N-terminal 25 residues of thymosin ␤ 4 , SDKPDMAEIEKFDKSKLKK-TETQEK-rhodamine. Human recombinant gelsolin was truncated to the N-terminal 406 residues (identified here as gelsolin segment 1-3) prior to expression so as to eliminate the dependence of F-actin binding on calcium (27).Anisotropy Assay-A standard curve showing the fluorescence anisotropy of a rhodamine-labeled thymosin ␤ 4 peptide (0.1 M) as a function of Mg 2ϩ -actin concentration in F buffer (5.0 mM Tris-HCl, 40 mM KCl, 2.0 mM MgCl 2 , 0.2 mM ATP, 0.2 mM dithiothreitol, 0.1 mM CaCl 2 , 0.125 mM EGTA, and 0.01% sodium azide, pH 7.8) was generated with vertically excited polarized light at 546 nm in an L or T format steady state fluorimeter. The KCl concentration was 8.0 mM for the experiments employing unlabeled thymosin ␤ 4 , and in this low salt buffer the standard curve as shown in Fig.…”
mentioning
confidence: 99%
“…5 In spite of the absence of strict regulation of the actin filament-severing ability of G1-G3, calcium ion binding to this fragment does influence its structure and activity, as demonstrated by a reduced hydrodynamic volume, diminished proteolytic susceptibility, and increased tryptophan fluorescence. 9,10 Isolated G1 experiences a three-orders of magnitude increase in affinity for actin in the presence of calcium ions, and the Ca 2C occupying its type II site is reported to be locked into the G1-actin structure, inaccessible to chelation by EGTA. 11 Furthermore, transient binding of Ca 2C to G2 is proposed to facilitate the activation process.…”
Section: Introductionmentioning
confidence: 99%